Penerimaan Pajak Kendaraan Bermotor di Tengah Pandemi: Studi Kasus BAPENDA Jawa Barat: Indonesia - Manalu, Herold Moody (Fakultas Ekonomi Universitas Advent Indonesia, 2024)
ABSTRACT. The Covid-19 pandemic has had various impacts on society in Indonesia. One of the impacts is a decrease in people's income which causes people not to carry out their responsibilities in paying taxes. One tax that has great potential for regional income is motor vehicle tax. This research aims to determine motor vehicle tax revenue in West Java Province before and during the Covid-19 pandemic. This research uses motor vehicle tax revenue data provided by the West Java Province Regional Revenue Agency for 2018-2022. The data used in this research consists of motor vehicle tax revenue data for the 24 months before Covid-19 and motor vehicle tax revenue for the 24 months during the Covid-19 period. Data analysis and data testing used the normality test, independent sample t test and t difference test. The comparison results of several regions in West Java show mixed results and the research results show that motor vehicle tax revenue before Covid-19 in West Java had a higher nominal value than motor vehicle tax revenue during the Covid-19 period, and the research results show that different tests carried out show that Covid-19 does not affect motor vehicle tax revenues in West Java province.